Women's empowerment to gender transformative change in agri-food systems in Fiji - Nath, Radhisha Shivnal; Alam, Mumtaz (Fiji National University, 2023)
The article takes a look at how gender transition might help advance women's empowerment within the context of Fiji's agri-food systems. Women's contributions to agriculture and food systems have always been vital, but structural inequalities have kept them from reaching their full potential. Recent efforts to improve women's empowerment in agri-food systems have mostly focused on expanding women's access to resources, markets, and knowledge. Unfortunately, these efforts have not done enough to tackle the root causes of gender inequality in agri-food systems. A 'gender transformative' approach, on the other hand, seeks to shift the underlying social norms, power relations, and institutional arrangements that sustain gender inequality. This article proposes that a gender transformative approach is necessary for Fiji to achieve sustainable and equitable agri-food systems. Using case studies from Fiji and elsewhere, this research highlights the potential benefits of a gender transformative strategy, such as increased productivity, better nutrition, and greater social inclusion. However, it acknowledges the challenges and complications of putting such a policy into effect, particularly in the face of cultural and economic hurdles. In order for Fiji to attain true gender equality and sustainable development in its agri-food systems, a gender transformative strategy is necessary, as argued in this article. It will take cooperation from government officials, nonprofits, and businesses for this to come to fruition. At the article's conclusion, suggestions are made for enacting a gender transformative strategy in agri-food systems, both in Fiji and worldwide.